2005
DOI: 10.1021/jf050183e
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of the Essential Oil of Cinnamomum zeylanicum and Eugenol in Peroxynitrite-Induced Oxidative Processes

Abstract: The essential oil obtained from the bark of Cinnamomum zeylanicum Blume (Lauraceae) and three of its main components, eugenol, (E)-cinnamaldehyde, and linalool (representing 82.5% of the total composition), were tested in two in vitro models of peroxynitrite-induced nitration and lipid peroxidation. The essential oil and eugenol showed very powerful activities, decreasing 3-nitrotyrosine formation with IC50 values of 18.4 microg/mL and 46.7 microM, respectively (reference compound, ascorbic acid, 71.3 microg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 31 publications
2
61
0
1
Order By: Relevance
“…CAR has shown anti-tumorigenic activity in hepatocellular carcinoma, both in vitro and in vi o [33,34]. Additional anti-in ammatory and antitumor activities of CAR have been reported [16,[18][19][20][21]. Jayakumar et al [33] showed that CAR pretreatment had protective e ect against diethylnitrosamine-induced hepatocellular carcinoma in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAR has shown anti-tumorigenic activity in hepatocellular carcinoma, both in vitro and in vi o [33,34]. Additional anti-in ammatory and antitumor activities of CAR have been reported [16,[18][19][20][21]. Jayakumar et al [33] showed that CAR pretreatment had protective e ect against diethylnitrosamine-induced hepatocellular carcinoma in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated that CAR exhibits antiin ammatory [15], anti-microbial [16] and anti-viral activities [17]. Anti-carcinogenic and anti-tumorigenic activity [16,18], and antioxidant properties [19][20][21] have also been attributed to CAR. A recent study conducted in rats demonstrated that CAR was not hepatotoxic at the applied dosage and, in fact, protected against ischemia/reperfusion-associated damage to the liver [22].…”
mentioning
confidence: 99%
“…Eugenol Main component of clove -Syzygium aromaticum (Jirovetz et al 2006) and cinnamon -Cinnamomum zeylanicum oils (Chericoni et al 2005). Used as a flavor, in dentistry as a local anesthetic, in the manufacture of vanillin and clandestine production of phenyllamines (Hunter 2009), and in perfumery for oriental and spicy notes (Bauer and Garbe 2001).…”
Section: Phenylpropanoidsmentioning
confidence: 99%
“…It has traditionally been used to treat toothache, fight bad breath and treatment common cold [6][7][8][9] . The bark of tree consists of volatile oil, possesses many medicinal properties like antibacterial, anti-oxidant, anti-ulcer, antidiabetic [10][11][12] and antifungal (Bruneton et al, 1998). Cinnamaldehye is the most prevalent with concentration of 6,000 -30,000 ppm 13,14 .…”
Section: Introductionmentioning
confidence: 99%